2016
DOI: 10.1007/s10995-016-2111-0
|View full text |Cite
|
Sign up to set email alerts
|

The Iodine Status of Queensland Preschool Children After the Introduction of Mandatory Iodine Fortification in Bread: An Exploratory Study Using a Convenience Sample

Abstract: Introduction Appropriate dietary iodine is essential for thyroid hormone synthesis, especially in young children. Following an iodine fortification in bread initiative, approximately 6 % of Australian preschool children were expected to have an excessive iodine status. The aim of this study was to document the current iodine status of preschool children using urinary iodine concentration (UIC) as a biomarker of iodine intake. Methods A convenience sample of fifty-one preschool children, aged 2-3 years, were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…There was, however, no difference in UIE between the different socioeconomic groups. These findings, along with those of other studies conducted post-fortification of bread with iodized salt [ 25 , 58 ], provide evidence that compared to pre-fortification data Australian schoolchildren are now iodine replete. Therefore, it appears that the iodine intakes of Australian schoolchildren have increased to sufficiency since the introduction of mandatory fortification of bread with iodized salt.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…There was, however, no difference in UIE between the different socioeconomic groups. These findings, along with those of other studies conducted post-fortification of bread with iodized salt [ 25 , 58 ], provide evidence that compared to pre-fortification data Australian schoolchildren are now iodine replete. Therefore, it appears that the iodine intakes of Australian schoolchildren have increased to sufficiency since the introduction of mandatory fortification of bread with iodized salt.…”
Section: Discussionsupporting
confidence: 65%
“…In order to combat the re-emergence of deficiency, mandatory fortification of all commercially-produced yeast-leavened bread, excluding organic bread, with iodized salt was implemented in 2009 [ 21 ]. Studies conducted post-fortification utilizing spot urine samples, including the 2011–2013 Australian Health Survey (AHS), have reported an improvement in iodine status among children and adults, when compared to pre-fortification [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the success of voluntary fortification of bread with iodised salt in Tasmania (19) , mandatory fortification of all commercially produced bread in Australia (excluding organic varieties) with iodised salt was implemented in 2009 (20) . Studies conducted post-fortification with the use of iodised salt in bread have observed an improvement in iodine status (21)(22)(23)(24)(25)(26)(27) .…”
mentioning
confidence: 99%